Non-esterified fatty acids as biomarkers of diet and glucose homeostasis in pregnancy: The impact of fatty acid reporting methods: NEFA reporting methods affect dietary and cardiometabolic endpoints. (January 2022) - Azab, Sandi M.; de Souza, Russell J.; Ly, Ritchie; Teo, Koon K.; Atkinson, Stephanie A.; Morrison, Katherine M.; Anand, Sonia S.; Britz-McKibbin, Philip
Highlights: This study demonstrates the utility of specific NEFAs and their sub-classes as viable dietary and clinical biomarkers when reported as their relative proportions. Consistently stronger dietary correlations were observed when expressed as mol%. Glucose intolerance was positively associated with odd chain NEFAs as expressed in µM but inversely associated when expressed as mol%. Monounsaturated NEFAs (µM and mol%) had robust positive associations with pre-pregnancy BMI, second trimester skin-fold thickness, glycated hemoglobin, fasting glucose, and glucose intolerance. More research is needed to investigate inconsistencies between absolute concentrations and relative proportions when reporting fatty acids. Abstract: Background: Sparse data exists on the utility of individual serum non-esterified fatty acids (NEFAs) as clinical and dietary biomarkers and how reporting methods could affect these associations. We investigated the associations of 19 serum NEFAs expressed as µM or mol%, with self-reported dietary intake data, and cardiometabolic health indicators in pregnant women. Methods: In this cross-sectional study, 273 pregnant women in their second trimester each completed a semi-quantitative food-frequency questionnaire and provided fasting serum samples. Comprehensive serum NEFA analysis was performed by multisegment injection-nonaqueous capillary electrophoresis-mass spectrometry. We evaluated the associations of NEFAs using two different reporting methods, with diet quality, specific foods intake, and measures of adiposity and glucose homeostasis. Results: Consistently stronger dietary correlations were observed when expressed as mol%. Serum ω -3 NEFAs were associated with diet quality and fish/fish oil daily servings (DHA mol%, r=  0.37; p  = 4.8e-10), and odd-chain NEFAs were associated with full-fat dairy intake (15:0 mol%, r  = 0.23; p  = 9.0e-5). Glucose intolerance was positively associated with odd chain NEFAs as expressed in µM ( r  = 0.21; p=  0.001) but inversely associated when expressed as mol% ( r  = −0.31; p=  2.2e-7). In contrast, monounsaturated NEFAs (µM and mol%) had robust positive associations with pre-pregnancy BMI, second trimester skin-fold thickness, glycated hemoglobin, fasting glucose, and glucose intolerance. Conclusions: This study demonstrates the utility of specific NEFAs and their sub-classes as viable dietary and clinical biomarkers when reported as their relative proportions. More research is needed to investigate inconsistencies between absolute concentrations and relative proportions when reporting fatty acids.